Penyajian Laporan Keuangan Syariah dan Non Syariah: Studi kasus pada Bank Rakyat Indonesia dan Bank Syariah Indonesia - Desta Saputra; Dewi Fadillah; Maryati Cina W; Maya Artika (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2024)
Financial statements are closely related to the field of accounting. Financial statements prepared by a company can be used as a tool for making internal managerial decisions as well as for external parties of the company. A company's financial statements can be analyzed using several financial ratios. Financial statements (Financial Statment) is the end product of a series of processes for recording and summarizing business transaction data, accountants are expected to be able to organize all accounting data so as to produce financial statements and even must be able to integrate and analyze the financial reports they make. Even the benchmark for whether or not a financial institution or company is healthy is seen from the financial statements and this will affect the decisions of external parties in terms of investment or others, in this case the author presents two financial statement materials as a comparison, namely conventional and sharia financial statements, where both have similarities and differences in many ways.